Meningkatkan Kemandirian Belajar Peserta Didik Kelas VII Melalui PBL Dalam PAK dan BP di SMPN 2 Siberut Tengah - Juliasman Satoko; Ansel Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Education is currently still believed to be a very effective medium in building independent learning. The learning independence that the author means in this research is related to a condition where students are able to process themselves in making decisions and are responsible for the actions they take. In this research, the author also uses the Problem Based Learning (PBL) learning model. So that the learning process is always related to Problem Based Learning (PBL) learning steps. To achieve the educational goals proclaimed by the government, the author as a Catholic Religious Education teacher wants to take part in it, namely by increasing the learning independence of students in PAK which the author experiences is still very minimal, especially for students who are in the Mentawai Islands Regency and especially class VII students at SMPN 2 Siberut Tengah, with the title class action research : "Increasing the learning independence of class VII students through PBL in PAK and BP at SMPN 2 Siberut Tengah". From the problem formulation, it can be seen that the objectives of this PTK are: 1) To find out how to increase the learning independence of Class VII students through PBL in PAK and BP at SMPN 2 Siberut Tengah?; 2) To find out the activities of teachers and students in the learning process through PBL in PAK and BP class VII at SMPN 2 Siberut Tengah? This type of research is a type of classroom action research carried out in class with two cycles of face-to-face action . The variables in this research are students' learning independence as the dependent variable (variable x) and variable y is the activities of teachers and students in the learning process through PBL in PAK and BP . The primary data source in this research is class VII students at SMPN 2 Central Siberut, Mentawia Islands Regency, who have taken Catholic religious lessons . To obtain this data, the techniques used are observation, tests and documentation. The Hypothesis Analysis and Testing technique is quantitative descriptive , namely comparing the level of learning independence before this research was conducted, namely the initial condition of students' learning independence , the increase in students' independence after action I (cycle I) and the increase in students' independence after action II (cycle II), then reflected. Based on the research results, it can be concluded that there has been an increase in the independence of phase D class VII students in each indicator by implementing the Problem Based Learning model in PAK and BP.